2017
DOI: 10.1080/08856257.2017.1386316
|View full text |Cite
|
Sign up to set email alerts
|

Measuring self-efficacy, aptitude to participate and functioning in students with and without impairments

Abstract: Including vulnerable groups of students such as students with learning disabilities in mainstream school research, require ethical considerations and adapting questionnaires to make these accessible. As a consequence these students are excluded, not studied as a separate group, or give inadequate replies. This pilot study aims at developing and evaluating student self-reported measures, rating aspects of student experiences of school-based Physical Education (PE). Instrument design, reliability and validity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Despite functional limitations, findings in this study indicate that all groups of students were equally engaged in PE. In addition, a strong relationship (r = 0.76) between PE specific self-efficacy and aptitude to participate was previously established (Bertills et al, 2018a). The significant associations found in the current study between student engagement and the self-reported questionnaires indicate that student perceived self-efficacy in PE and aptitude to participate are also reflected in observed student engagement during PE lessons.…”
Section: Individual Contextual and Environmental Factors Influencinsupporting
confidence: 73%
See 1 more Smart Citation
“…Despite functional limitations, findings in this study indicate that all groups of students were equally engaged in PE. In addition, a strong relationship (r = 0.76) between PE specific self-efficacy and aptitude to participate was previously established (Bertills et al, 2018a). The significant associations found in the current study between student engagement and the self-reported questionnaires indicate that student perceived self-efficacy in PE and aptitude to participate are also reflected in observed student engagement during PE lessons.…”
Section: Individual Contextual and Environmental Factors Influencinsupporting
confidence: 73%
“…Earlier findings show that the teacher is one vital factor to the inclusive classroom climate, since teacher-students relationships affect student-student relationships (Falkmer, 2013) and a positive classroom climate fosters student engagement (Furrer and Skinner, 2003). It has also been suggested that PE-teachers' ratings of the classroom climate, serve as a social indicator of how students experience their learning environment and is most beneficial to students with disabilities, compared to peers with typical function (Bertills et al, 2018a). By positioning themselves in communicative proximity to their students, teachers may increase opportunities for individualized instructions, feed-back and feed-forward, but also affect the classroom climate positively by supplying support to those in need to overcome barriers and balance functional restrictions (Giangreco et al, 1997).…”
Section: Individual Contextual and Environmental Factors Influencinmentioning
confidence: 99%
“…Following a checklist manual with quality standards (Mokkink et al 2010), psychometric properties of the instruments were evaluated in a pilot-study. The scales were found to be accessible, valid and reliable (Bertills, Granlund, and Augustine 2017). Moderate correlations between the self-efficacy and functioning scales indicated that they measured different aspects of ability and competence.…”
Section: Student Questionnairesmentioning
confidence: 91%
“…Student questionnaires (see Supplementary Material ) were evaluated in a trial study ( Bertills et al, 2018a ). Internal consistency, factor structure, and relations between measures were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, longitudinal approaches are needed to study the directionality of relationships and stability of scores and provide insight to developmental trends ( Sabiston et al, 2014 ) of students’ self-reported experiences in early adolescence. Moreover, students with disabilities need to be studied as a separate group ( Bertills et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%